ANALISIS TINDAK TUTUR ILOKUSI DALAM CERPEN TAK TERLIHAT KARYA NUGIBARA - Delsa Jelita Putri (University of Brawijaya, 2025)
This study analyzes illocutionary acts in Nugibara's short story Tak Terlihat. Illocutionary acts are acts of speech by the speaker that serve to state or inform something and are used to get the interlocutor to perform an action. The purpose of this study is to identify and describe the types of illocutionary acts that appear in the short story based on Searle's theory of speech acts. The research method used is qualitative descriptive. The data used in this study are sentences containing illocutionary acts in Nugibara's short story Tak Terlihat. The data collection technique was carried out by recording existing documents, with the first step being to repeatedly read the object to be studied, namely the short story Tak Terlihat by Nugibara. Second, the illocutionary acts in the short story were classified, and the implicatures contained in the acts of speech in the short story were analyzed. The results of the study show that various types of illocutionary acts are found in the short story Tak Terlihat, including representative, directive, expressive, commissive, and declarative acts. This study is expected to provide a deeper understanding of the function and meaning of illocutionary acts in literary works, especially short stories, as well as enriching pragmatic studies in discourse analysis.